Three chemosensory proteins from the sweet potato weevil, Cylas formicarius, are involved in the perception of host plant volatiles. Issue 10 (7th June 2021) - Hua, Jinfeng; Fu, Yujie; Zhou, Qiaoling; Huang, Yongmei; Li, Huifeng; Chen, Tianyuan; Ma, Daifu; Li, Zongyun
Abstract: BACKGROUND: Chemosensory proteins (CSPs) play important roles in chemical communication, but their precise physiological functions are still unclear. Cylas formicarius is the most serious pest attacking sweet potato around the world. At present, there is no effective way to control this pest. RESULTS: Our results showed that CforCSP1, 5 and 6 genes were highly expressed in the antennae of both sexes of C. formicarius . In addition, results from a fluorescence competitive binding assay showed that the CforCSP1, 5 and 6 proteins had high binding affinities for 17 plant volatiles including eight host plant volatiles. This indicated that the three proteins may be involved in the detection of host plant volatiles. Furthermore, results from four‐arm olfactometer bioassays showed that there was a significant tendency for C. formicarius to be attracted to eucalyptol, β ‐carotene, benzaldehyde, vanillin and phenethyl alcohol, while it was repelled by β ‐ionone. Finally, the levels of expression of the three CforCSPs in C. formicarius were successfully inhibited by RNA interference (RNAi). Behavioral experiments showed that CforCSP1, 5 and 6 ‐deficient C. formicarius were partly anosmic to β ‐cyclocitral, benzaldehyde, octyl aldehyde, and β ‐ionone and exhibited a reduced ability to locate the host plant volatiles β ‐carotene and vanillin. CONCLUSION: Our data suggest that CforCSP1, 5 and 6 likely are involved in the chemical communication between C. formicarius and host plant volatiles, which may play pivotal roles in oviposition and feeding site preferences. More importantly, these results could provide information for the development of monitoring and push‐pull strategies for the control of C. formicarius . © 2021 Society of Chemical Industry. Abstract : Chemosensory proteins play important roles in chemical communication in insects, but their precise physiological functions are still unclear. Cylas formicarius is the most serious pest attacking sweet potato around the world. At present, there is no effective way to control this pest. Our data suggest that CforCSP1, CforCSP5 and CforCSP6 are likely involved in the chemical communication between C. formicarius and host plant volatiles, which may play pivotal roles in oviposition and feeding site preferences. More importantly, these results could provide information for the development of monitoring and push‐pull strategies for the control of C. formicarius.